An Investigation of Blood Cholesterol Level during Starvation Stress In Clarias Batrachus - Prasad, Nayan K. (Tribhuvan University Journal, 2016)
Cholesterol is an organic lipid molecule synthesized by all animal cells. It is an essential structural component of the cell membrane in all animals that is required to maintain both membrane structural integrity and fluidity. Cholesterol also serves as a precursor for the biosynthesis of steroid hormones, bile acids, and vitamin D. In the present investigation, the level of blood cholesterol has been estimated in both the sexes of Clariasbatrachus, which were subjected to starvation for 40 days. Cholesterol content was estimated by Sackett's Method (1925). Clariasbatrachus adapted well to starvation stress and survived all throughout the experimental period. The blood cholesterol concentration was higher in females than in males both under normal and starved conditions. After 10 days of starvation, the blood cholesterol dropped about 23 percent in male and about 21 percent in female. After30 days of starvation, more than 70 percent drop was observed in male while it was only 55 percent in female. Similarly, after 40 days of starvation the males showed more decrease (88%) than that of females(76%). The bar notation of the recorded data showed that the drop between 0 and 10, 0 and 20, 0 and 30, 0 and 40 and among 10, 20, 30and 40 days of starvation were highly significant at 1 percent of P for blood cholesterol.